Mutu Dimensi Jaminan Pelayanan Kesehatan dalam Peningkatan Kepuasan Pelanggan di RSU DR. H. Koesnadi Bondowoso - Mohammad Henri Wahyono; Ancah Caesarina Novi Marchianti; Sebastiana Viphindrartin (Pascasarjana Universitas Jember, 2018)
The main focus of KARS 2012 hospital accreditation is the quality of patient care and safety. The decreasing of Satisfaction Index of Public in Stroke Pojok RSU room dr. H. Koesnadi Bondowoso from the fourth quarter of 2016 by 78.1% and in the first quarter of 2017 to 76.63% showed a decrease in customer satisfaction ever treated in the space. So with this research is expected to know the assessment of the community as a service user stroke corner about the quality of service received. This research is a qualitative study with case study approach conducted from April to December 2017. This research focuses on assurance dimension as one dimension of health service by using three assessment indicators, covering the ability of officer in giving service, actions to be performed and the preservation of patient privacy. The main informants in this study were 10 people from the patient's family who were being treated and the additional informant was 2 nurse stroke corner. From this research, it is found that officer of stroke corner has different ability and skill, stroke corner officer always keep patient privacy and officer always ask permission (inform concent) before doing action. In conclusion that most informants expressed satisfaction with the service guarantee provided by the stroke corner room. Keyword: Stroke, Stroke Corner, Satisfaction, Assurance